Reading for Evidence and Interpreting Visualizations in Mathematics and Science Education - Norris, Stephen P.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
CRYSTAL$1 (BAlberta was established to research ways to improve students$1 (Bunderstanding and reasoning in science and mathematics. To accomplish this goal, faculty members in Education, Science, and Engineering, as well as school teachers joined forces to produce a resource bank of innovative and tested instructional materials that are transforming teaching in the K-12 classroom. Many of the instructional materials cross traditional disciplinary boundaries and explore contemporary topics such as global climate change and the spread of the West Nile virus. Combined with an emphasis on the use of visualizations, the instructional materials improve students$1 (Bengagement with science and mathematics. Participation in the CRYSTAL$1 (BAlberta project has changed the way I think about the connection between what I do as a researcher and what I do as a teacher: I have learned how to better translate scientific knowledge into language and activities appropriate for students, thereby transforming my own teaching. I also have learned to make better connections between what students are learning and what is happening in their lives and the world, thereby increasing students$1 (Binterest in the subject and enriching their learning experience.s
Keywords: Education; Education; Education (general).